Nutritional Intake in Children with Septic Shock: A Retrospective Single-Center Study - Kirk, Angela H. P.; Ong, Chengsi; Wong, Judith J.-M.; Loh, Sin Wee; Mok, Yee Hui; Lee, Jan Hau (Journal of Pediatric Intensive Care, 2021)
Nutritional practice in children with severe sepsis or septic shock remains poorly described. We aimed to describe nutrition received by children with severe sepsis or septic shock and explore the association of nutritional intake with clinical outcomes. This study was a retrospective study of children who required pediatric intensive care unit (PICU) admission from 2009 to 2016. Outcomes were mortality, ventilator-free days (VFDs), and PICU-free days (IFDs). A total of 74 patients with septic shock or severe sepsis were identified. Forty-one (55.4%) patients received enteral nutrition (EN) only, 6 (8.1%) patients received parental nutrition (PN) only, 15 (20.3%) patients received both EN and PN, and 12 (16.2%) patients received intravenous fluids alone. Eight of 74 (10.8%) and 4 of 74 (5.4%) had adequate energy and protein intake, respectively. Patients who received early EN had lower odds of 28-day mortality (adjusted hazard ratio [HR] = 0.09, 95% confidence interval [CI]: 0.02, 0.45, p = 0.03) more 28-day VFDs (adjusted β-coefficient = 18.21 [95% CI: 11.11, 25.32], p < 0.001), and IFDs (adjusted ß-coefficient = 16.71 [95% CI: 9.86, 23.56], p < 0.001) than patients who did not receive EN. Late EN was also associated with lower odds of mortality, more VFDs, and IFDs compared with no EN (HR = 0.06, 95% CI: 0.02, 0.23; p < 0.001; adjusted β coefficient = 15.66, 95% CI: 9.31, 22.02; p < 0.001; and 12.34 [95% CI: 6.22, 18.46], p < 0.001; respectively). Inadequate calories and protein were not associated with mortality. EN in children with septic shock or severe sepsis was associated with improved clinical outcomes. Future prospective studies are required to explore the impact of EN timing and optimal nutritional intake in these children.
Keywords: enteral nutrition; septic shock; pediatric intensive care unit; critically ill children